O conhecimento por acquaintance em Bertrand Russell - Borchate, Denise (2015)
The acquaintance is the relation between the mind and certain objects called russell´s objects. These objects are restricted to individuals who can think directly. Appearances, such as colors, are examples of russell´s objects. The acquaintance is a primitive epistemic relation. The individual has the ability to discriminate those objects, distinguishing them from others in the traditional interpretation of acquaintance. The objects are known by acquaintance in the sense that the mind can identify them perfectly. In this case, the subject can not be wrong about the interpretation and the knowledge of what is thinking about it. A individual can, however, be in a relation with one and the same individual at different times, not realizing that it is the same. The cases of the continuous phenomena show that, explaining the difficulty in demonstrating the reference equality through changes in the character of the experience.